EFFECTIVE METHODS FOR DEVELOPING PROFESSIONAL SKILLS IN FUTURE DRAFTING (TECHNICAL DRAWING) TEACHERS (American Journal of Interdisciplinary Research and Development, 2025)
This article describes some pedagogical aspects of developing the professional competence of future teachers and their effective impact on the education system.